2001
DOI: 10.1093/bja/87.6.870
|View full text |Cite
|
Sign up to set email alerts
|

Transtracheal high frequency jet ventilation for endoscopic airway surgery: a multicentre study

Abstract: Serious complications during high frequency jet ventilation (HFJV) are rare and have been documented in animals and in case reports or short series of patients with a difficult airway. We report complications of transtracheal HFFJV in a prospective multicentre study of 643 patients having laryngoscopy or laryngeal laser surgery. A transtracheal catheter could not be inserted in two patients (0.3%). Subcutaneous emphysema (8.4%) was more frequent after multiple tracheal punctures. There were seven pneumothorace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
73
1
11

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(88 citation statements)
references
References 33 publications
1
73
1
11
Order By: Relevance
“…It has been reported that the incidence of barotrauma during PTJV is as high as 10%. 23 These complications were mainly associated with incorrect insertion of the ventilation catheter. With our system, the operator can visualize the tip of the ventilation catheter during ventilation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the incidence of barotrauma during PTJV is as high as 10%. 23 These complications were mainly associated with incorrect insertion of the ventilation catheter. With our system, the operator can visualize the tip of the ventilation catheter during ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…19 In such a case, intra-alveolar pressure can be as high as the driving pressure of jet ventilation. Therefore, catastrophic events may occur including pneumothorax 23,24 and cardiac arrest 25 due to unrecognized upper airway obstruction during PTJV. In this new system, ventilation is performed via a video-laryngoscopy inserted into the pharyngeal cavity ensuring an open pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the TTJV recommended by the ASA practice guidelines for difficult airway management, [6] the use of SJV in difficult airway management has the following two advantages: 1) Early use of jet ventilation immediately after direct laryngoscopy reduces the chance of hypoxia while allowing for longer times for tracheal intubation as patients are oxygenated and ventilated throughout the process; 2) Non-invasive jet ventilation reduces the possible complications of barotraumas compared to TTJV [11]. Thus, the new SJV technique we have introduced is expected to reduce the chance of the "cannot ventilate and cannot intubate" emergent difficult airway as patients was oxygenated and ventilated through SJV rather than a mask, and theoretically reduce morbidity and mortality related to difficult airway management.…”
Section: Discussionmentioning
confidence: 99%
“…Other complications of TTJV include bleeding, pneumothorax, barotrauma, tracheal and esophageal perforation as well as lifethreatening intravascular misplacement of the catheter. (12)(13)(14) In addition, when TTJV was placed emergently instead of prophylactically, complications were twice as likely to occur. (11) In order to avoid these complications it is of the utmost importance to check the proper position of the catheter before the initiation of jet ventilation by confirming the ability of free-air aspiration with a large syringe.…”
Section: Discussionmentioning
confidence: 99%